The Illustrated London News, 1842-2003. - Illustrated London News (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2025)
Containing over 250,000 images, this fascinating and visually stunning collection brings together the extensive back catalogue of one of the most influential and successful publications in the history of British print media: The Illustrated London News (ILN), founded in 1842 by Herbert Ingram. Whilst working as a newsagent and printer two consumer trends caught his attention: that papers featuring woodcut engraved illustrations tended to sell better and that people frequently requested "London news", as opposed to a specific publication. Developments in printing technology, such as faster rotary presses, helped Ingram translate his vision of "illustrated news" into a reality.
Date range: 1842-2003.
Keywords: Illustrated London news; London (England) -- History -- Periodicals; London (England) -- Social conditions -- Periodicals; Great Britain -- History -- Periodicals; Journalism -- Great Britain -- History